Sistem Monitoring Dan Deteksi Dini Terjadinya Gempa Berbasis Iot (Internet Of Things) - Fatimah, Fitri; Abdy, Sahara; Ramadhany, Sri; Fitriani, Pristiwati; Afifudin (Journal of Informatics Management and Information Technology, 2025)
Designing and developing systems capable of monitoring ground tremors in real-time and providing early warning before major earthquakes occur, increasing speed and accuracy in detecting potential earthquakes. This technology is known as an Internet of Things (IoT)-based earthquake monitoring and early detection system that uses motion sensors. To detect seismic activity, the system uses several motion sensors connected to the Internet of Things network. These motion sensors measure changes in ground vibration and transmit the data to a central server, which will process it to detect possible earthquakes. This research uses a methodology consisting of several stages. First, primary data is collected from motion sensors located in various earthquake-prone locations. This data is sent to a central server over the internet network. Furthermore, digital signal processing algorithms are used to analyze data to distinguish normal ground tremors from those that can signal earthquakes. This algorithm was created to identify suspicious changes in the intensity and frequency of ground vibrations. The system then sends a warning or notification to the user's device, such as a smartphone or computer, if a potential earthquake is detected. According to BMKG (Meteorology, Climatology, and Geophysics Agency) Earthquake intensity scale (GIS) states the impact caused by earthquakes. This scale is arranged more simply by having only five levels, namely I-V, where each level has its own meaning, level I is marked with white and level II is marked with green and level III is marked with yellow and level IV is marked with orange and the last level V is marked with red, and each level has its own meaning. The results show that the designed system can detect vibrations with high accuracy and provide early warning within seconds after suspicious seismic activity is detected. In addition, this system has a speed of sending data from the sensor to the server and good performance in the use of the internet network. IoT-based motion sensors allow for broader and decentralized monitoring of earthquakes. So, this Internet of Things-based earthquake monitoring and early detection system can be a good solution to improve earthquake disaster preparedness. By applying these technologies in different earthquake-prone areas, they can help spread and respond to potential earthquakes more quickly